Theory and practice of model transformations first International Conference, ICMT 2008, Zürich, Switzerland, July 1-2, 2008 : proceedings - ICMT 2008 (Lecture notes in computer science ;)
This book constitutes the refereed proceedings of the First International Conference on Theory and Practice of Model Transformations, ICMT 2008, held in Zurich, Switzerland, in July 2008. The 17 revised full papers presented were carefully reviewed and selected from 54 submissions. The scope of the contributions ranges from theoretical and methodological topics to implementation issues and applications. The papers include different issues related with: process and engineering of model transformations; model transformations supporting concurrency and time; matching and mapping within model transformation rules; language support for model transformation reuse and modularity; and correctness and analysis of model transformations. Process and engineering of model transformations -- Transformations have to be developed rest assured -- Lifting transformational models of product lines: a case study -- Model synchronisation: definitions for round-trip engineering -- The epsilon transformation language -- Model transformations supporting concurrency and time -- Transforming process algebra models into UML state machines: bridging a semantic gap? -- On specifying and visualising long-running empirical studies -- Programmed graph rewriting with time for simulation-based design -- Matching and mapping within model transformation rules -- Live model transformations driven by incremental pattern matching -- Semantics-based weaving of UML sequence diagrams -- Translation of QVT relations into QVT operational mappings -- Language support for model transformation reuse and modularity -- Composition techniques for rule-based model transformation languages -- Approaches for model transformation reuse: factorization and composition -- Code generation by model transformation -- Application of reflection in model transformation languages -- Correctness and analysis of model transformations -- Proofs-as-model-transformations -- Analysing graph transformation rules through OCL -- Extracting object interactions out of software contracts using model transformations.